Color variation of Lessonia trabeculata macroalgae dehydrated with infrared ray dryer - Castro Arata, Daphne H. (2022)
Fishmeal concentrates a high percentage of protein and its monetary cost is relatively high, searching for possible alternatives in macroalgae for improvement purposes is an option. Color is a fundamental characteristic of food, however, drying by the Infrared method as an emerging technology for the study of the macroalga Lessonia trabeculata is little studied. For this reason, the degradation and change of color in the drying process by infrared rays (IR) at different temperatures 40°C, 55°C and 70°C were objectively characterized with the color space scale (CIE-L*a *b*), through the use of a spectrophotometer. Drying was carried out with infrared rays in an infrared radiant heating chamber with a power of 4.5kW, 20.5 Amps. The results indicate that the best color treatment determined was for the macroalga Lessonia trabeculata at a temperature of 40°C with values ​​for: L*= 44.758±0.227, a*= -1.564 ± 0.016 and b*= 11.050±0.017; obtaining a first order kinetics for logarithmic scale corresponding to the parameters L*.b* as a function of time, likewise an activation energy value of Ea = 24.062 KJ/mol and the Arrhenius constant k0 = 0.0197 min- was reached. one. It is concluded that there is inverse variability between the color of the macroalgae and the temperature applied in the drying process; being the values ​​of the color parameters L*, a*, b* of the macroalga decreases as the temperature increases, thereby leading to color degradation.